SAT0569 Impact of bariatric surgery on rheumatic diseases: a systematic review and meta-analysis. (12th June 2018) - Moly, M.; Combe, B.; Barnetche, T.; Daien, C.; Gaujoux-Viala, C.; Lukas, C.; Morel, J.; Hua, C.
Abstract : Background: Obesity increases the incidence of rheumatic diseases. 1–3 Bariatric surgery (BS), is known to improve obesity-related comorbidities. 4 Objectives: The aim of our study was to assess current literature on the impact of BS on rheumatic diseases. Methods: We systematically searched literature (via Pubmed, Embase, Cochrane library and abstracts from recent ACR and EULAR meetings) for studies evaluating the effects of BS on musculoskeletal disorders and, more precisely, on auto-immune inflammatory rheumatic disorders (AIRD), osteoarthritis and gout. Whenever methodologically feasible and relevant, a meta-analysis was performed with Review Manager Software, with random effects models in case of heterogeneity. Data were extracted by one investigator and independently checked by another. Results: The literature search revealed 399 articles of potential interest, and further examination resulted in 119 studies included in systematic review (SR) and 24 studies fulfilling required criteria for preplanned meta-analysis. According to SR, BS seems to improve AIRD outcomes with notably 1 study on rheumatoid arthritis showing improvement in disease activity scores after BS and 2 studies showing a reduced incidence of psoriatic arthritis in patients who had BS compared to either general population or patients with psoriasis. Studies on patients with musculoskeletal disorders (mainly osteoarthritis but also undefined musculoskeletal pain) showed an improvement of physical function and pain after BS with pooled mean difference of −468.1 (95% confidence interval [95% CI] −646.8; −289.5) for WOMAC function score, −95.2 [-127.1; −63.3] for WOMAC pain score, 30.5 [22.0; 38.9] for SF36 physical function score, 22.9 [16.6; 29.2] for SF36 bodily pain score (figure 1). Meta-analysis on osteoarthritis surgical management (hip or knee arthroplasty) did not show significant differences between patients who had undergone BS and obese patients without previous BS: pooled Odd ratio (OR) for incidence of orthopaedic reoperation was 1.4 [0.88; 2.3] and pooled OR for incidence of post-operative prosthesis infection was 0.91 [0.53; 1.6]. Hyperuricemia frequency (effect size 0.83 [0.79; 0.87]) and uric acid levels (mean difference −1.5 [-2.0; −0.94]) were significantly decreased after BS. Two studies showed a decrease in gout flares after BS. Conclusions: Despite heterogeneity, our study supports the benefit of BS on several parameters for obese patients presenting with rheumatic diseases. References: [1] Lee R, Kean WF. Obesity and knee osteoarthritis. Inflammopharmacology2012;20:53–8. [2] Qin B, Yang M, Fu H, Ma N, Wei T, Tang Q, et al. Body mass index and the risk of rheumatoid arthritis: a systematic review and dose-response meta-analysis. Arthritis Res Ther2015;17:86. [3] Juraschek SP, Miller ER, 3rd, Gelber AC. Body mass index, obesity, and prevalent gout in the United States in 1988–1994 and 2007–2010. Arthritis Care Res2013;65:127–32. [4] Sjöström L, Lindroos AK, Peltonen M, Torgerson J, Bouchard C, Carlsson B, et al. Swedish Obese Subjects Study Scientific Group. Lifestyle, diabetes, and cardiovascular risk factors 10 years after bariatric surgery. N Engl J Med2004;351:2683–93. Disclosure of Interest: None declared